IMPLIKASI KEBIJAKAN POLITIK EKONOMI PARTAI TERHADAP TINGKAT ELEKTABILITAS PARTAI DALAM PEMILU (Studi Kasus pada 5 Pemilihan Umum Legislatif di Indonesia dari tahun 1997 s.d. 2014) - LISMAN SETIAWAN (Politika: Jurnal Ilmu Politik, 2016)
ABSTRACTThe mission of all political parties in the election is maximizing votes. The number of votes in the elections is a tool to measure the electability of a political party. Economic voting theory tells that government parties are held more accountable than opposition parties for the economic conditions. If economic conditions near election is good, people votes for the incumbents, otherwise for the opposition. Exchange rate can be used to measure the economic conditions of a nation on a daily basis. This research reveals the causal relationship between the result of parties’ political economic policy in welfare which is measured by the exchange rate, against the parties electability in the election which is measured by the number of votes. First, this research is try to find the relation between exchange rate amd parties electability, and then try to find the voter type that most dominant and majority in Indonesia’s elections and last, try to find the fastest, most effective and most efficient parties political economic policy in Indonesia.Keyword : political party, exchange rate, number of votes